Dietary heme-enriched Corynebacterium extract exerts health benefits by reshaping gut microbiota - Lee, Seungki; Cho, Youngjin; Park, Sehyeon; Park, Kyung Hoon; Kim, Mihye; Lee, Seohyeon; Cha, Min Jeong; Chang, Suhwan; Yoon, Hyunjin; Kim, Pil (Food Bioscience, 2024)
We previously reported that a heme-enriched Corynebacterium extract (hSCP) alleviated weight gain and lowered subcutaneous fat mass in a murine model. To understand the mechanisms underlying the beneficial effects of dietary hSCP, we investigated the histological and microbiological changes in the guts of mice after hSCP administration in this study. Dietary hSCP lowered serum triglyceride and cholesterol levels and restrained adipose tissue expansion in mice fed a normal diet (ND) or a high-fat diet (HFD). The colonic mucosa was prominently lined with acidic and neutral mucin-enriched goblet cells and Muc2 transcription was increased by dietary hSCP in HFD-fed mice. Given the nutritional content of hSCP, microbial shifts triggered by dietary hSCP were dissected from the cecum and colon of the mice. Bacterial community compositions in the luminal contents were significantly reshaped by hSCP supplementation in HFD-fed mice and also differed between intestinal loci, that is, the cecum and colon. Dietary hSCP enriched short-chain fatty acid-producing bacterial genera in ND-fed mice, while attenuating other mucin-degrading bacteria in HFD-fed mice. The addition of hSCP to a co-culture of a defined microbiota community promoted Lactobacillus gasseri proliferation compared with nine other species. An in vitro culture medium supplemented with hSCP increased bile salt hydrolase activity and cholesterol assimilation by L. gasseri, which is reminiscent of the beneficial effects of Lactobacillus spp. as cholesterol-lowering probiotics. Our findings demonstrate the potential of hSCP as a dietary supplement with beneficial effects on lipid metabolism and gut health.
Keywords: Gut health; Gut microbiota; hSCP; Lipid metabolism